Impact of emergency physician experience on decision-making in patients with suspected community-acquired pneumonia and undergoing systematic thoracic CT scan. Issue 8 (24th June 2019) - Le Bel, Josselin; Pelaccia, Thierry; Ray, Patrick; Mayaud, Charles; Brun, Anne-Laure; Hausfater, Pierre; Casalino, Enrique; Benjoar, Mikhael; Claessens, Yann-Erick; Duval, Xavier
Abstract : Objectives: To determine whether the impact of a thoracic CT scan on community-acquired pneumonia (CAP) diagnosis and patient management varies according to emergency physician's experience (≤10 vs >10 years). Methods: Early thoracic CT Scan for Community-Acquired Pneumonia at the Emergency Department is an interventional study conducted from November 2011 to January 2013 in four French emergency departments, and included suspected patients with CAP. We analysed changes in emergency physician CAP diagnosis classification levels before and after CT scan; and their agreement with an adjudication committee. We performed univariate analysis to determine the factors associated with modifying the diagnosis classification level to be consistent with the radiologist's CT scan interpretation. Results: 319 suspected patients with CAP and 136 emergency physicians (75% less experienced with ≤10 years, 25% with >10 years of experience) were included. The percentage of patients whose classification was modified to become consistent with CT scan radiologist's interpretation was higher among less-experienced than experienced emergency physicians (54.2% vs 40.2%; p=0.02). In univariate analysis, less emergency physician experience was the only factor associated with changing a classification to be consistent with the CT scan radiologist's interpretation (OR 1.77, 95% CI 1.01 to 3.10, p=0.04). After CT scan, the agreement between emergency physicians and adjudication committee was moderate for less-experienced emergency physicians and slight for experienced emergency physicians (k=0.457 and k=0.196, respectively). After CT scan, less-experienced emergency physicians modified patient management significantly more than experienced emergency physicians (36.1% vs 21.7%, p=0.01). Conclusions: In clinical practice, less-experienced emergency physicians were more likely to accurately modify their CAP diagnosis and patient management based on thoracic CT scan than more experienced emergency physicians. Trial registration number: NCT01574066